The Introduction of Learning Organization in Selected Malaysian Organizations: A Comparative Case Study - Ahmad, Abd Rahman (2000)
Little concern has been given to discover the deeper meanings and intricacies of learning organization, although this term has been widespread and has gained attention in a number of Malaysian organizations. The main concern of this study was to generate insight to the understanding of the perspectives of learning organization, its implementations and challenges in selected Malaysian organizations. Specifically, the objectives of the study were: (1) to gain insight and understanding of the concepts of learning organization in selected organizations ; (2) to understand how the selected organizations take steps to implement learning organization; and (3) to understand the challenges faced by the selected organizations in the implementation of learning organization. Multiple qualitative case study approach was used to answer the research objectives. Data were collected through interviews, observations and analysis of formal documents from the selected organizations. The findings of this study were obtained from both within-case analysis and cross-case analysis. For within-case analysis, the description of three organizations selected was described individually. Whereas, for the cross-case analysis the description compared the findings from each of the three organizations selected. Several methods were used to check the validity and reliability of this study. Three methods : 'triangulation', 'member check' and 'peer examination technique' were employed to check the internal validity. External validity was checked by using multisite approach. To increase reliability, this study used the triangulation process, graduate committee review and audit trail. This study found that although the understanding and implementation of learning organization was at the beginning stage in each of the organizations, the result showed some evolving ideas occurred throughout the three organizations . All the three organizations showed the understanding of the concepts of learning organization, its implementation and challenges were based on their own identity. Organization A, being a technical service and development organization, seemed to be more Western-oriented approach. Organization B, which was involved in agriculture and food research and development, was more concerned with experimental activities that related to the Japanese approach. Organization C was a Malay-dominated organization inculcated with Islamic values assimilated both Western and Japanese approaches into the local approach, labeled as the Islamic approach. As a conclusion, the study clarified the understanding of the concepts, its implementation and challenges of learning organization in the selected organizations. The study also identified some guidelines for coping with challenges in implementing learning organization within the three selected organizations. The study recommended that the three organizations should continue their efforts in developing their organizations towards becoming full-pledge learning organizations.